The influence of stigma on PrEP uptake among adolescent girls and young women in Johannesburg, South Africa and Mwanza, Tanzania: Qualitative findings from the EMPOWER study - Anne L. Stangl; Caitlin Bryan; Iman Barré; Lethabo Ramskin; Shelley Lees; Nomhle Ndimande-Khoza; Deborah Baron; Manuela Colombini; Sheila Harvey; Saidi Kapiga; Fiona Scorgie; Sinéad Delany-Moretlwe (PLoS ONE, 2026)
Background Adolescent girls and young women (AGYW) in sub-Saharan Africa need HIV prevention options. Stigma may impede uptake and consistent use of oral pre-exposure prophylaxis (PrEP). We sought to understand how stigma manifested and influenced decisions of AGYW participating in a PrEP demonstration trial in Johannesburg, South Africa and Mwanza, Tanzania. Methods This paper reports on serial qualitative in-depth interviews (IDI) with AGYW (n = 39) as well as healthcare providers and community stakeholders (n = 30) conducted during a randomized controlled trial that evaluated the effect of empowerment clubs to address harmful gender norms and stigma on PrEP persistence in AGYW aged 16–24 in South Africa and Tanzania. Analysis was thematic and inductive. Results Stigma manifested in two main ways: HIV-related stigma and sexual behavior stigma. PrEP was often mistaken for antiretroviral therapy, and some participants taking daily PrEP reported that partners or family members thought they were living with HIV. Anticipated PrEP sexual stigma was common and linked with concerns around AGYW being perceived as promiscuous. While most participants anticipated stigma related to PrEP use, experiences of stigma were rare and did not deter AGYW from initiating PrEP. Many participants demonstrated resilience and remained confident in their decision to use PrEP and some developed strategies to avoid stigma, such as hiding pills or taking PrEP when partners or family members were not around. Conclusions Our findings suggest that anticipated stigma is a common yet surmountable concern of AGYW initiating PrEP in eastern and southern Africa. Future PrEP implementation should be paired with multi-level activities to reduce stigma including empowerment activities for adolescents, strategies to reduce negative attitudes among health care providers and community-wide education to raise awareness and position PrEP as a responsible choice for young people to protect their health. Trial registration Pan African Clinical Trials Registry PACTR202006754762723.